Spremljanje kakovosti hlodovine s konvencionalnimi, dendrokronološkimi in nedestruktivnimi metodami - Straže, Aleš (Les (Ljubljana), 2023)
European oak logs (Quercus robur, Quercus petraea) from the 15th auction of valuable logs in Slovenj Gradec in 2021 were included in the study. Of the 1,318 auctioned logs, 78 were randomly selected and visually graded into quality classes (A, B, C) according to the National Grading Rules (2017). In parallel, we analysed the wood growth dendrochronologically and the acoustic properties of the logs using the longitudinal vibration resonance method. The logs with the best quality had a larger diameter and, on average, wider annual rings. We confirmed the correlation between the visually determined quality and the obtained price of the logs. Longitudinal vibration velocity (v) and relative acoustic conversion efficiency (RACE) were positively correlated with log quality and price. The frequency spectra of the low-quality logs differed from the theoretical spectra. This study confirms the feasibility of non-destructive acoustic methods for evaluating oak log quality.
Keywords: cena; European oak; hrast; kakovost; les; logs grading; nedestruktivno testiranje; non-destructive evaluation; price; quality; razvrščanje hlodovine; wood